Generating near-field fresnel diffraction patterns by iterative fresnel integrals method: a computer simulation approach - Abedin, Kazi Monowar; Rahman, S.M.M.; Haider, A F M Yusuf (© 2012 Nova Science Publishers, Inc., 2017)
This book chapter was published in the book Computer Simulations: Technology, Industrial Applications and Effects on Learning [© 2012 Nova Science Publishers, Inc.] and the definite version is available at: https://www.novapublishers.com/catalog/product_info.php?products_id=36502